PSNR Based levels Evaluation of FCM Algorithm with Peak and Valley Filtering Based Brain Images (International Journal of Food and Nutritional Sciences, 2022)
In this paper, a new segmentation algorithm with the integration of peak-and-valley filtering based denoising and Gaussian kernels based fuzzy c-means (PVFCM) algorithm is proposed for medical image segmentation. First, the image is denoised by using the peak-and-valley filtering algorithm. Secondly, image segmentation algorithm with Gaussian kernels based fuzzy c-means is performed on the denoised image. The performance of the proposed algorithm is tested on OASIS-MRI image dataset. The performance is tested in terms of PSNR,Score, Number of iterations (NI) and Execution time (TM) under different Gaussian noises on OASIS-MRI dataset. The results after investigation, the proposed method shows a significant improvement as compared to other existing methods in terms of PSNR Score, NI and TM under different Gaussian noises on OASIS-MRI dataset.